Combinatorial identities on binomial coefficients and harmonic numbers - Chu, Wenchang; Yan, Qinglun (Utilitas Mathematica, 2008)
By means of partial fraction decomposition and binomial inversions, we review a useful pair of classical binomial identities. Their connection with harmonic numbers is further investigated through finite difference method. Several interesting identities on binomial coefficients and harmonic numbers are established via combination of derivative operator and symmetric functions.